2018
DOI: 10.20892/j.issn.2095-3941.2017.0136
|View full text |Cite
|
Sign up to set email alerts
|

Parkin protein expression and its impact on survival of patients with advanced colorectal cancer

Abstract: Objective:Features of colorectal cancer such as natural history, molecular, chromosomal, and epigenetic alterations have been well described. However, there is still a lack of accurate prognostic markers, which is evident by the lower overall survival rates of patients with advanced cancer. Although alterations in parkin protein expression have been described in colorectal cancer, the functional significance of this protein remains unknown. The present study aimed to investigate the involvement of parkin expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Interestingly, some colorectal cancer cell lines contain mutated forms of PRKN and may use alternate mechanisms to activate mitophagy [38]. Research is starting to investigate how PRKN may be used as a prognostic marker in CRC as it may correlate with invasion and overall survival [39].…”
Section: Autophagy Subtypesmentioning
confidence: 99%
“…Interestingly, some colorectal cancer cell lines contain mutated forms of PRKN and may use alternate mechanisms to activate mitophagy [38]. Research is starting to investigate how PRKN may be used as a prognostic marker in CRC as it may correlate with invasion and overall survival [39].…”
Section: Autophagy Subtypesmentioning
confidence: 99%
“…Although the precise association between PARK2 and cancer susceptibility is not well-understood, the deletion, copy number alteration, mutations, and protein expression of PARK2 have been found in several types of cancers, such as glioblastoma, breast, ovarian, liver, colorectal, and lung (15, 1725). Xiong et al have identified PARK2 mutation as a single genetic susceptibility factor for lung cancer (19) and it could become an independent prognostic marker in advanced colorectal cancer (26). Inactivation of PARK2 may play a critical role in carcinogenesis (27).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the expression of PRKN is prognostic in patient outcome. Decreased PRNK expression is correlated with increased survival ( 57 ); however, increased expression is found with enhanced invasion in tumors ( 57 ). Our work highlights that the dual nature of autophagy and mitophagy in cancer growth could be attributed to available nutrient status.…”
Section: Discussionmentioning
confidence: 99%